Comparison of antibody level after SARS-CoV-2 infection in case of home treated and hospital treated patients - Chowdhury, Indira; Mishu, Farzana Akonjee; Alam, Mohammad Masum; Yasmin, Rubina; Rahman, Mohammad Matiur; Mollah, Forhadul Hoque (BIRDEM Medical Journal, 2021)
Background:The severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has spread throughout the world causing a serious health issue. After the swine flu pandemic (also known as H1N1) of 2009-10, WHO had declared Coronavirus disease 2019 (COVID-19) as a global pandemic. This pandemic caused huge losses to the entire world. Most of the patients with mild symptoms were treated at home but patients with difficulty in breathing and various complications were treated at the hospital. Naturally produced antibodies or vaccination can only offer protection. The objective was to compare the antibody status after SARS-CoV-2 infection in hometreated and hospital-treated patients. Methods: This cross-sectional study was conducted in the Department of Biochemistry and Molecular Biology, BIRDEM General Hospital, from July, 2020 to June, 2021. A total of 77 patients (age 18 – 70 years) infected by SARS-CoV-2 were enrolled for this study. Among them, 37 were home treated and 40 were treated in hospital. The study subjects were non-vaccinated. For this study, serum IgG level was measured by the automated analyser. For statistical analysis, the Mann Whitney U test was done. Results:The median value of serum IgG was significantly higher in hospital-treated patients than in hometreated patients (p < 0.001). Hospital treated patients with a history of comorbidity developed more amount of antibody in comparison to home treated patients. Conclusion:Hospital treated patients develop higher antibodies in comparison to home treated patients. BIRDEM Med J 2022; 12(1): 11-15